A low voltage load balancing distribution method considering street information and V2G technology application - Lu, Youfei; Gong, Yushen; Huang, Chenhui; Gu, Shaoyuan; Tong, Jiapeng; Huang, Wendong (Frontiers in Energy Research, 2024)
The low-voltage distribution network is the final stage in delivering electric energy from power plants to consumers. Its operational condition significantly affects numerous power users. Distribution companies can implement intelligent planning through comprehensive digital systems, effectively preventing load distribution imbalances for medium-voltage and high-voltage distribution networks. However, in the case of low-voltage distribution networks (LVDNs), resolving load imbalance issues typically relies on planners' experience, which poses significant limitations. Vehicle-to-grid (V2G) technology utilizes electric vehicle (EV) batteries as distributed energy storage units, enabling bidirectional energy and information exchange between the vehicle and the power grid. With advancements in EV charging technology, EVs can now actively participate in the operation of lowvoltage distribution networks (LVDNs) through V2G technology. This paper proposes a low-voltage load distribution planning method incorporating street information and V2G technology. A two-stage stochastic programming mixed-integer model is developed to address the issue of imbalanced loads in the low-voltage distribution network. The planning scheme is derived by solving this model. Finally, a case study is presented to verify the effectiveness of the proposed method.